Increasing the distance of attentional focus improves free throw accuracy in male basketball players - sarhan, aiman (Journal of Physical Education, 2024)
Basketball requires a distinctive blend of physical strength and technical skill, where exceptional players are set apart by their precision, accuracy, and ability to handle the ball. The objective of this study is to examine how various external focus instructions affect the accuracy of shooting free throws for inexperienced male basketball players. The objective is to offer valuable knowledge to coaches and players in order to enhance methods of training to improve free throw accuracy.Methods the study involved 40 male participants aged 18-25 assigned to Distal External Focus, Proximal External Focus, Internal Focus and Control Group. Participants performed a pretest block followed by 5 acquisition blocks with specific focus instructions. Each block consisted of 5 throws. Shooting accuracy was measured using the registration system of (VaezMosavi and Rostami, 2009). Statistical analysis was done using SPSS version 20, which included a mixed Paired T-Test and One-Way Anova to compare the group performances. Results the group of participants with a distal external focus (M = 8.68) consistently obtained the highest scores, followed by the group with a proximal external focus (M = 6.46), while the internal focus (M = 4.84) and control groups (M = 4.88) had the lowest scores.Conclusion the study demonstrates that using distal external focus instructions improves free throw shooting accuracy considerably when compared to instructions of proximal external focus, internal focus or no specific focus instruction. These discoveries offer valuable perspectives for maximizing motor abilities and improving free throw shooting precision in basketball.